Arabidopsis N6-methyladenosine methyltransferase FIONA1 regulates floral transition by affecting the splicing of FLC and the stability of floral activators SPL3 and SEP3. (28th November 2022) - Cai, Jing; Hu, Jianzhong; Amara, Umme; Park, Su Jung; Li, Yuxia; Jeong, Daesong; Lee, Ilha; Xu, Tao; Kang, Hunseung
Abstract: N 6 -methyladenosine (m 6 A) RNA methylation has been shown to play a crucial role in plant development and floral transition. Two recent studies have identified FIONA1 as an m 6 A methyltransferase that regulates the floral transition in Arabidopsis through influencing the stability of CONSTANS ( CO ), SUPPRESSOR OF OVEREXPRESSION OF CONSTANS 1 ( SOC1 ), and FLOWERING LOCUS C ( FLC ). In this study, we confirmed that FIONA1 is an m 6 A methyltransferase that installs m 6 A marks in a small group of mRNAs. Furthermore, we show that, in addition to its role in influencing the stability of CO, SOC1, and FLC, FIONA1-mediated m 6 A methylation influences the splicing of FLC, a key floral repressor, and the stability of SQUAMOSA PROMOTER-BINDING PROTEIN-LIKE 3 ( SPL3 ) and SEPALLATA3 ( SEP3 ), floral activators, which together play a vital role in floral transition in Arabidopsis. Our study confirms the function of FIONA1 as an m 6 A methyltransferase and suggests a close molecular link between FIONA1-mediated m 6 A methylation and the splicing of FLC and the destabilization of SPL3 and SEP3 in flowering time control. Abstract : FIONA1 is a novel mRNA N 6 -methyladenosine methyltransferase that regulates floral transition by influencing the splicing of FLC, a key floral repressor, and the stability of SPL3 and SEP3, floral activators, in Arabidopsis.